VALUASI EKONOMI OBJEK WISATA PANTAI CAROCOK PAINAN DENGAN TRAVEL COST METHOD, CONTINGENT VALUATION METHOD, DAN INCOME APPROACH KABUPATEN PESISIR SELATAN - , Ade Marlina ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This study entitled \"Economic Valuation Carocok Beach Attractions Painan with Travel Cost Method, Contingent Valuation Method and Income Approach in Kabupaten Pesisir Selatan\". The purpose of this study was to determine the economic value of Carocok beach attractions Painan assessed with the travel cost method, contingent valuation method and income approach and to investigate the factors that influence the number of visits and respondents' willingness to pay for Carocok Beach. The data used in this study is primary data in the form of questionnaire results from 110 respondents. Equipped also with secondary data is data the number of foreign tourists and domestic visitors (2005-2013) who visited to Kabupaten Pesisir Selatan , data on the number of visitors who visit Carocok Beach (2006-2013). Data collected regressed negative binomial regression using the travel cost method and use ordinary least squares to the contingent valuation method and using the discounted cash flow approach to the income approach. The results of this study showed two things. 1. Economic value Carocok Beach attraction using. a. Travel cost method approach, generating economic value is in the range Rp267.775.187.556,- up to Rp473.890.477.197,- with an average of Rp370.832.626.521,- per year. b. Contingent valuation method approach, generating economic value in the range Rp4.024.475.025,- up to Rp12.073.425.075,- with an average economic value Rp7.244.055.045,-. c. Income approach generates economic value for Carocok Beach is Rp167.217.252.934,-. 2. Factors that influence the number of visits to Carocok Beach based travel cost method are travel cost variable and time variable are negative and significant effect on the number of visits, while the perceived quality variable positive and significant effect on the number of individual visits. Based on the contingent valuation method, factors that affect the willingness to pay of visitors to the attraction are travel costs variable and a significant negative effect on the willingness to pay of individuals and income variable a significant positive effect on willingness to pay individuals for Carocok Beach attraction.